2015
DOI: 10.5301/jbm.5000125
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 Mutation Analysis and its Correlation with Clinicopathological Features and Prognosis in Colorectal Cancer Patients

Abstract: There was no strong association between patient prognosis and FBXW7 mutations in our large-scale study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
3
30
1
Order By: Relevance
“…Low FBXW7 expressions in tumor as compared to normal tissues were significantly correlated with poor prognosis of overall survival in CRCs and esophageal cancer (EC) patients (Iwatsuki et al, 2010; Kurashige et al, 2012). A similar pattern of low overall survival was also found in early stage CRC patients with FBXW7 mutants but the results was not significant when compare to wild type patients (Chang et al, 2015). About 10 to 11% of FBWX7 alterations were found in most of CRCs studies (Eliana et al, 2013; Grim, 2014; Cai Z.X.…”
Section: Discussionsupporting
confidence: 62%
“…Low FBXW7 expressions in tumor as compared to normal tissues were significantly correlated with poor prognosis of overall survival in CRCs and esophageal cancer (EC) patients (Iwatsuki et al, 2010; Kurashige et al, 2012). A similar pattern of low overall survival was also found in early stage CRC patients with FBXW7 mutants but the results was not significant when compare to wild type patients (Chang et al, 2015). About 10 to 11% of FBWX7 alterations were found in most of CRCs studies (Eliana et al, 2013; Grim, 2014; Cai Z.X.…”
Section: Discussionsupporting
confidence: 62%
“…Mutations in the FBXW7 gene are thought to impair cyclin E degradation resulting in unchecked cellular growth, and subsequently in progression of CRC (115)(116)(117). The frequency of FBXW7 mutation in the present study was 3% in Arab patients, none were found in the matched Western cohort.…”
Section: Discussionmentioning
confidence: 60%
“…S582L was noted in six cases (14%) and was the third most common FBXW7 mutation in our study. Chang et al [33] reported a similar frequency of FBXW7 mutations (7.5%, 114/1519) in CRC patients but noted that Ser 582 (S582L) was the most frequent type (19.3%), ahead of Arg 465 (R465H, 16.6%), Arg 505 (R505C, 14.9%), and Arg 479 (R479Q, 14.9%). These variations are slight and within the realm of inter-study statistical variations.…”
Section: Discussionmentioning
confidence: 96%
“…In a study of 1,519 patients with CRC at all stages, Chang et al [33] showed that FBXW7 mutations did not impact prognosis. In fact, in that study, subgroup analyses of FBXW7 mutations showed that R465H, R465C, and R479Q were associated with better 5-year OS rates than other FBXW7 mutation types were (76.9% vs 56.0%; p=0.012).…”
Section: Discussionmentioning
confidence: 99%